Developing a tool for mapping adult mental health care provision in Europe: the REMAST research protocol and its contribution to better integrated care - Luis Salvador-Carulla; Francesco Amaddeo; Mencía R. Gutiérrez-Colosía; Damiano Salazzari; Juan Luis Gonzalez-Caballero; Ilaria Montagni; Federico Tedeschi; Gaia Cetrano; Karine Chevreul; Jorid Kalseth; Gisela Hagmair; Christa Straßmayr; et al. (International Journal of Integrated Care, 2015)
Introduction: Mental health care is a critical area to better understand integrated care and to pilot the different components of the integrated care model. However, there is an urgent need for better tools to compare and understand the context of integrated mental health care in Europe. Method: The REMAST tool (REFINEMENT MApping Services Tool) combines a series of standardised health service research instruments and geographical information systems (GIS) to develop local atlases of mental health care from the perspective of horizontal and vertical integrated care. It contains five main sections: (a) Population Data; (b) the Verona Socio-economic Status (SES) Index; (c) the Mental Health System Checklist; (d) the Mental Health Services Inventory using the DESDE-LTC instrument; and (e) Geographical Data. Expected results: The REMAST tool facilitates context analysis in mental health by providing the comparative rates of mental health service provision according to the availability of main types of care; care placement capacity; workforce capacity; and geographical accessibility to services in the local areas in eight study areas in Austria, England, Finland, France, Italy, Norway, Romania and Spain. Discussion: The outcomes of this project will facilitate cooperative work and knowledge transfer on mental health care to the different agencies involved in mental health planning and provision. This project would improve the information to users and society on the available resources for mental health care and system thinking at the local level by the different stakeholders. The techniques used in this project and the knowledge generated could eventually be transferred to the mapping of other fields of integrated care.